2019
DOI: 10.1111/exsy.12374
|View full text |Cite
|
Sign up to set email alerts
|

Developing a personal value analysis method of social media to support customer segmentation and business model innovation

Abstract: Companies need to find out about the personal values of customers and identify customer segments before developing effective business models (BMs) or marketing strategies. Therefore, understanding the personal values of customers is critical in BM design. Traditional personal value evaluation methods are laborious and time‐consuming. In recent years, social media have become an important platform for people to share ideas and express views, making the presence of a huge amount of opinions on platforms that can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In addition to these studies, there are many studies conducted in recent years regarding customer segmentation (Chen et al, 2019;Funk et al, 2021;Abu-Bakar et al, 2021;Moon et al, 2021;Hedhilia et al, 2021;Špička & Zdeňka, 2022;Budhathoki et al, 2022;Wang et al, 2022;Caracciolo et al, 2022;Vigneau et al, 2022;Carla Kuesten et al, 2022). It has been observed that these studies on customer segmentation are mostly about organic products, food, and supplements.…”
Section: Business Andmentioning
confidence: 99%
“…In addition to these studies, there are many studies conducted in recent years regarding customer segmentation (Chen et al, 2019;Funk et al, 2021;Abu-Bakar et al, 2021;Moon et al, 2021;Hedhilia et al, 2021;Špička & Zdeňka, 2022;Budhathoki et al, 2022;Wang et al, 2022;Caracciolo et al, 2022;Vigneau et al, 2022;Carla Kuesten et al, 2022). It has been observed that these studies on customer segmentation are mostly about organic products, food, and supplements.…”
Section: Business Andmentioning
confidence: 99%
“…The advantages of Weka are therefore the analysis and application of the entire process of machine learning, from data pre-processing, creating a model by choosing one of many realized machine learning algorithms, and making predictions based on input data. Many researchers have used this tool because of its intuitive user interface and easy way to get results from a trained model [33][34][35][36][37][38].…”
Section: Analysis Of Existing Solutionsmentioning
confidence: 99%
“…Association rule mining is one of the descriptive data mining analyzes, which is first introduced by Agrawal et al (1993). Association rule mining can find interesting relations and dependencies between variables in large databases (Chen et al, 2019). Then, the identification of these significant associations is helpful for many decision-making processes in business contexts (Weng and Huang, 2018;Medina-Serrano et al, 2019;Nguyen et al, JEC 16,1 2021).…”
Section: Related Workmentioning
confidence: 99%